A popular code for the annunciation in Medieval English lyrics - Kowalik, Barbara (Adam Mickiewicz University, 2006)
The paper deals with a popular type of the Annunciation lyric in medieval English poetry. A brief survey of the role of the angelic announcement to Mary in medieval art and culture is given. The argument then pursues several distinctive traits of this kind of lyric in a number of poems from the thirteenth through the sixteenth centuries. The distinguishing features include a tripartite structure, a common set of words, phrases, ideas and images, emphasis on singing, a spring setting, tryst between lovers, and the use of popular genres, particularly ballads and carols. By analogy with music, it is argued that a certain popular code for the Annunciation existed, against which interesting artistic transformations of the theme were introduced. For example, the Annunciation was evoked in a highly compressed and allusive manner by means of but a few elements of the code. The principal elements of the alleged code derived from popular art and imagination. Their application to theological issues frequently led to the blurring of boundaries between the sacred and the profane, and between the Christian and the pagan. The paper proposes a distinction between Lent and alleluia subtypes of the Annunciation lyric. It also demonstrates how the pastourelle, aubade, and chanson d’aventure conventions of secular love poetry were adapted to represent the Annunciation. Finally, it suggests a connection between the lyric “At a spryng wel” and a specific statue of the Blessed Virgin Mary, like the much-reverenced statue of Our Lady at Walsingham.